Development of a technological method for selecting the composition of multicomponent agrophytocenoses in the soil and climatic conditions of the Astrakhan region - Galina K. Bulakhtina; Natalia V. Tyutyuma (Мелиорация и гидротехника, 2025)
Purpose: to develop a technological method for selecting the composition of multicomponent agrophytocenoses in an arid climate on light chestnut soils of the Astrakhan region. Materials and methods. The field experiment on a technological method development for selecting the composition of multicomponent agrophytocenoses was conducted by employees of the department of sustainable use of natural resources on natural pastures with a very high degree of degradation in the Chernoyarsk district Astrakhan region in the period 2019–2023. The experiment had four options: spring-summer pasture (belt of Leafless Calligonum trees and interseeding – Crested Wheatgrass, Forage Kochia and Montpellier Camphor-Fume); autumn-winter pasture (belt of Eurotia, in row-spacing – Wheatgrass, Kochia, Camphor-Fume, Oriental Saltwort, Shogon); all-year pasture (belt of Eurotia, in row-spacing – Wheatgrass, Kochia, Camphor-Fume, Oriental Saltwort, Shogon, Paletsky Saltwort); control – natural pasture. The experimental program was compiled according to the “Methodology of field experiment” by B. A. Dospekhov (1985); the calculation of the energetic feed unit (EFU) in the forage mass was performed according to the methodology of the L. K. Ernst Federal Research Center for Animal Husbandry, the calculation of the norm of the load of farm animals on pastures was performed by the A. A. Kutuzov and et al. methodological guidelines (1995). Results. All created agrophytocenoses exceeded the productivity of the natural pasture (control) by 2.8–3.8 from the first year of vegetation (September), and by the fifth year – by an average of 20 times. The amount of EFU in 1 kg of pasture fodder of agrophytocenoses exceeded the control on average by 3.5 times from the first year and by the fifth year – by 14 times. Conclusions. Various life forms of plants in the agrophytocenoses, including grasses, sub-shrubs and shrubs, allowed plants to most fully master the habitat and collect a greater amount of exchange energy (5–6 times) and ensure an increase in the livestock output per unit area.